Ruptured Landscapes Landscape, Identity and Social Change - Sooväli-Sepping, Helen; Reinert, Hugo; Miles-Watson, Jonathan (Landscape Series, 2015)
This volume breaks new ground in the study of landscapes, both rural and urban. The innovative notion of this landscape collection is rupture. The book explores the ways in which societal, economic and cultural changes are transforming the meanings and understandings of landscapes. The text explores both how landscapes are contesting changes in society and, changing society. The volume combines empirically fine-grained accounts of landscape rupture, from different parts of the world, with a sustained effort to explore, rethink and analytically extend the concept of rupture itself. In order to move landscape study beyond its Eurocentric focus, the text juxtaposes accounts of socio-cultural change within the West with conceptual as well as empirical material from outside of Europe. The case studies explored in the volume are drawn from Europe, Asia and the Americas. Under the joint heading of landscape rupture, the chapters explore a timely and impressively diverse range of current global issues: from species extinction and industrial pollution, to ethnic and sectarian violence, religious conflict and the management of colonial or military legacies in a postcolonial age. The book combines fresh empirical data with innovative theoretical approaches to open understanding of landscape as a dynamic, living entity subject to abrupt change and unpredictable disruptions. Through this dual reflection the volume is able to provide a powerful demonstration of the possibilities that are available for human action, social change and material landscape to combine.